An Overview of the Malaria Control Programme in Zambia. (9th December 2012) - Chanda, Emmanuel; Kamuliwo, Mulakwa; Steketee, Richard W.; Macdonald, Michael B.; Babaniyi, Olusegun; Mukonka, Victor M.
Abstract : The Zambian national malaria control programme has made great progress in the fight against Malaria. The country has solid, consistent, and coordinated policies, strategies, and guidelines for malaria control, with government prioritizing malaria in both the National Health Strategic Plan and the National Development Plan. This has translated into high coverage of proven and effective key preventive, curative, and supportive interventions with concomitant marked reduction in both malaria cases and deaths. The achievements attained can be attributed to increased advocacy, communication and behaviour changes, efficient partnership coordination including strong community engagement, increased financial resources, and evidence-based deployment of key technical interventions in accordance with the national malaria control programme policy and strategic direction. The three-ones strategy has been key for increased and successful public-private sector partner coordination, strengthening, and mobilization. However, maintaining the momentum and the gains is critical as the programme strives to achieve universal coverage of evidence-based and proven interventions. The malaria control programme's focus is to maintain the accomplishments, by mobilizing more resources and partners, increasing the government funding towards malaria control, scaling up and directing interventions based on epidemiological evidence, and strengthen active malaria surveillance and response to reduce transmission and to begin considering elimination.